Axonal Excitability Does Not Differ between Painful and Painless Diabetic or Chemotherapy‐Induced Distal Symmetrical Polyneuropathy in a Multicenter Observational Study. Issue 4 (7th March 2022) - Themistocleous, Andreas C.; Kristensen, Alexander G.; Sola, Roma; Gylfadottir, Sandra S.; Bennedsgaard, Kristine; Itani, Mustapha; Krøigård, Thomas; Ventzel, Lise; Sindrup, Søren H.; Jensen, Troels S.; Bostock, Hugh; Serra, Jordi; et al.
Abstract : Objective: Axonal excitability reflects ion channel function, and it is proposed that this may be a biomarker in painful (vs painless) polyneuropathy. Our objective was to investigate the relationship between axonal excitability parameters and chronic neuropathic pain in deeply phenotyped cohorts with diabetic or chemotherapy‐induced distal symmetrical polyneuropathy. Methods: Two hundred thirty‐nine participants with diabetic polyneuropathy were recruited from sites in the UK and Denmark, and 39 participants who developed chemotherapy‐induced polyneuropathy were recruited from Denmark. Participants were separated into those with probable or definite neuropathic pain and those without neuropathic pain. Axonal excitability of large myelinated fibers was measured with the threshold tracking technique. The stimulus site was the median nerve, and the recording sites were the index finger (sensory studies) and abductor pollicis brevis muscle (motor studies). Results: Participants with painless and painful polyneuropathy were well matched across clinical variables. Sensory and motor axonal excitability measures, including recovery cycle, threshold electrotonus, strength–duration time constant, and current–threshold relationship, did not show differences between participants with painful and painless diabetic polyneuropathy, and there were only minor changes for chemotherapy‐induced polyneuropathy. Interpretation: Axonal excitability did not significantly differ between painful and painless diabetic or chemotherapy‐induced polyneuropathy in a multicenter observational study. Threshold tracking assesses the excitability of myelinated axons; the majority of nociceptors are unmyelinated, and although there is some overlap of the "channelome" between these axonal populations, our results suggest that alternative measures such as microneurography are required to understand the relationship between sensory neuron excitability and neuropathic pain. ANN NEUROL 2022;91:506–520